Beneficial Bacteria in the Intestines of Housefly Larvae Promote Larval Development and Humoral Phenoloxidase Activity, While Harmful Bacteria do the Opposite - Zhang, Qian; Wang, Shumin; Zhang, Xinyu; Zhang, Kexin; Li, Ying; Yin, Yansong; Zhang, Ruiling; Zhang, Zhong (Frontiers in Immunology, 2022)
The gut microenvironment of houseflies provides unique conditions for microbial colonization. Some gut microorganisms provide benefits for the development of the host by regulating the interaction between the host and intestinal pathogens. Gut microbial alterations can stimulate the host's immune mechanism to resist pathogen invasion and affect the development of insects. In this study, we isolated 10 bacterial strains from housefly larval intestines. The isolated bacteria were added to the larval diet to analyze the effects of microecological regulation of gut bacteria on larval development. Dynamic changes in gut flora composition after oral administration of specific bacteria were analyzed although 16S rRNA gene high-throughput sequencing technology. To explore the interaction between gut bacteria and the host, the immune response of larvae against the invasion of foreign microorganisms was observed through a phenoloxidase activity experiment. Our results showed that the oral administration of various isolated bacteria had different effects on larval development. Oral administration of beneficial bacteria, including Enterobacter hormaechei, Klebsiella pneumoniae, Acinetobacter bereziniae, Enterobacter cloacae, Lysinibacillus fusiformis and Bacillus safensis, promoted larval development by increasing gut community diversity and the humoral immunity of larvae, while harmful bacteria, including Pseudomonas aeruginosa, Providencia stuartii and Providencia vermicola, influenced larval development by inhibiting the growth of beneficial bacteria and reducing the humoral immunity of larvae. The beneficial bacteria isolated in our research could be applied as good probiotic additives for the intensive feeding of larvae, while isolation of the harmful bacteria provides a basis for the development of pest inhibitors. Furthermore, our research revealed the immune response of housefly phenoloxidase to exogenous microorganism stimulation, providing richer and more comprehensive knowledge of the larval innate immune response.